Travel information exchanges in a computer-mediated environment : a social network analysis of the Africa category on the Departure Lounge branch of the Thorn Tree - De Waal, Martha (University of Pretoria, 2013)
Thesis (DPhil (Information Science))--University of Pretoria, 2007.